(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Exploring the development of relevant directions for improving efficiency, economic calculation, and fostering innovation in the management of medical services lays the foundation for transformative enhancements in healthcare delivery, operational effectiveness, and patient outcomes. This comprehensive article will delve deep into specific strategies, technologies, and methodologies that drive efficiency, economic sustainability, and innovation within medical service management, offering insights into key areas of improvement and avenues for advancement in the healthcare industry.